2021
DOI: 10.3389/fmicb.2021.633075
|View full text |Cite
|
Sign up to set email alerts
|

Host Phylogeny and Diet Shape Gut Microbial Communities Within Bamboo-Feeding Insects

Abstract: The gut microbiome plays an important role in a host’s development and adaption to its dietary niche. In this study, a group of bamboo-feeding insects are used to explore the potential role of the gut microbiota in the convergent adaptation to extreme diet specialization. Specifically, using a 16S rRNA marker and an Illumina sequencing platform, we profiled the microbial communities of 76 gut samples collected from nine bamboo-feeding insects, including both hemimetabolous (Orthoptera and Hemiptera) and holome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 84 publications
(110 reference statements)
2
38
0
Order By: Relevance
“…We have several potential explanations for the observed variation in bacterial diversity and composition among native and invasive leaf miners. First, host physiochemical conditions and feeding habits vary among species, impacting the community composition of microbiota ( 26 , 54 , 55 ). The native species L. chinensis is oligophagous, while the three invasive Liriomyza species are highly polyphagous ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have several potential explanations for the observed variation in bacterial diversity and composition among native and invasive leaf miners. First, host physiochemical conditions and feeding habits vary among species, impacting the community composition of microbiota ( 26 , 54 , 55 ). The native species L. chinensis is oligophagous, while the three invasive Liriomyza species are highly polyphagous ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbiota composition is known to vary among host species, sex, and developmental stages, and these differences have been generally attributed to host-specific selection 15 , 32 , 46 . Host morphology and physiochemical conditions vary among species and developmental stages, impacting the community structure of microbiota 12 , 16 , 32 . Thus, despite sympatric or adjacent wild stonefly species sharing the same or similar environmental conditions, various morphological and physiochemical differences may explain their different fungal community composition.…”
Section: Discussionmentioning
confidence: 99%
“…4 ), suggesting that other environmental factors are involved in shaping stonefly fungal community composition. For instance, several previous studies have demonstrated that diet also plays a substantial role in microbial diversity and composition 8 , 16 19 . Given that the diet of different stonefly species varies significantly from pollen to leaf fragments, detritus, lichen, and animal matter 42 44 , 51 , it could be speculated that host diet might explain certain aspects of microbiome diversity and composition among stonefly taxa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jesús M. et al confirmed that different time scales strongly influence the diversity, composition and metabolic capabilities of Brithys crini gut microbial communities [ 34 ]. Huang et al confirmed that both phylogeny and diet can impact the structure and composition of gut microbiomes [ 35 ]. The grasshoppers collected in this experiment were all adult, and the location and time were close to each other.…”
Section: Discussionmentioning
confidence: 99%